Combined heat and power economic dispatch using exchange market algorithm. (November 2016) - Ghorbani, Naser
Highlights: This paper proposes the exchange market algorithm for solving the CHPED problems. The proposed algorithm is successfully implemented on 5 convex and nonconvex CHPED problems. The results of proposed algorithm are compared with other intelligent algorithms. The results show that this algorithm can be utilized as an efficient and reliable tool in solving CHPED problem. Abstract: Combined heat and power economic dispatch (CHPED) is one of the critical issues in power systems, playing key role in economic performance of the system. CHPED is a challenging optimization problem of non-linear and non-convex type. Thus, evolutionary and heuristic algorithms are employed as effective tools in solving this problem. This paper applies newly proposed exchange market algorithm (EMA) on CHPED problem. EMA is a powerful and robust algorithm. With two powerful absorbing operators pulling solutions toward optimality and two smart searching operators, EMA is able to extract optimum point in optimization problem. In order to examine the proposed algorithm's capabilities and find optimum solution for CHPED problem, several test systems considering valve-point effect, system power loss and system constraints are optimized. The obtained results prove high capability of EMA in extracting optimum points. The results also show that this algorithm can be utilized as an efficient and reliable tool in solving CHPED problem.